2017
DOI: 10.1002/cbin.10908
|View full text |Cite
|
Sign up to set email alerts
|

In vitro treatment with concentrated growth factors (CGF) and sodium orthosilicate positively affects cell renewal in three different human cell lines

Abstract: The aim of this study was to investigate the in vitro effect of Silicon, in the soluble form of sodium orthosilicate, combined and not with the concentrated growth factors (CGF), a platelet-rich preparation, on three different human cell lines of fibroblasts (NHDF), endothelial cells (HUVEC), and osteoblasts (HOBs). Each cell type was treated with sodium orthosilicate at the final concentration of 0.5 mM and 1 mM, CGF, and sodium orthosilicate combined with CGF, for 72 h. At the end of the experimental period,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 48 publications
(107 reference statements)
0
21
0
Order By: Relevance
“…After dehydration and mounting with DPX, cells were detected using light microscopy. Digitally fixed images were produced and analyzed using a dedicated image software (Image Pro-Premier, Immagini & Computer, Milan, Italy) and the Integrated Optical Density (IOD) was measured and normalized to cell number [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…After dehydration and mounting with DPX, cells were detected using light microscopy. Digitally fixed images were produced and analyzed using a dedicated image software (Image Pro-Premier, Immagini & Computer, Milan, Italy) and the Integrated Optical Density (IOD) was measured and normalized to cell number [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…Undifferentiated HOB (without extracellular calcium deposits) were slightly reddish, whereas mineralized osteoblasts (with extracellular calcium deposits) were bright orange-red. Digitally fixed images of cells were analyzed using an image analyzer (Image Pro-Premier, Immagini & Computer, Milan, Italy) and the Integrated Optical Density (IOD) was measured and normalized to cell number [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…By summarising the results of the above‐mentioned clinical case treatment and in vitro coculture of HaCaT cells with CGF membrane, we propose the possible mechanisms for CGF gel or membrane in treating chronic ulcers as follows: Possible mechanisms that promote the generation of granulation tissue: In the process of producing CGF gel, fractional centrifugation can cause platelets to release their growth factors and cytokines, which can facilitate wound healing The stem cells and monocytes present in the CGF gel can move to the bottom of the wound, proliferate, and differentiate further into macrophages to facilitate wound healing …”
Section: Discussionmentioning
confidence: 99%
“…Rodella et al also demonstrated the existence of CD34 positive cells in CGF. CGF stimulates the cell growth, proliferation and metabolic activity of many different cell types in vitro [33], and CGF has also increased graft angiogenesis and wound healing around the sites of implants in vivo [34,35]. Masuki et al found that the platelet-rich fibrin clot exudates resulted in reduced levels of growth factors [15].…”
Section: Discussionmentioning
confidence: 99%